2022
DOI: 10.5603/imh.2022.0012
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of hepatitis B virus infection in a seafarer: an omitted problem of maritime medicine

Abstract: Infection with hepatitis B virus (HBV), despite the implementation of extensive preventive measures, has remained one of the biggest health problems worldwide. There are still people not covered by the compulsory vaccination programme and carriers of an actively replicating virus among professionally active seafarers. The article is based on a case report of a seafarer with life-threatening reactivation of long-term uncontrolled HBV infection that resulted in decompensated cirrhosis and liver transplant. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…For instance, it has been observed that seafarers are carriers of a number of prevalent silent infections. Examples of diseases affecting seafarers include HIV, hepatitis B, and sexually transmitted infections (Muli et al, 2010;Pougnet et al, 2020;Rokicki et al, 2022). There are numerous different types of infections, with a particular emphasis on events that first happen onboard ships (Table 1).…”
Section: Outbreak Of Disease On Shipmentioning
confidence: 99%
“…For instance, it has been observed that seafarers are carriers of a number of prevalent silent infections. Examples of diseases affecting seafarers include HIV, hepatitis B, and sexually transmitted infections (Muli et al, 2010;Pougnet et al, 2020;Rokicki et al, 2022). There are numerous different types of infections, with a particular emphasis on events that first happen onboard ships (Table 1).…”
Section: Outbreak Of Disease On Shipmentioning
confidence: 99%